Socio-Economic Assessment on Flood Risk Impact: A Methodological Review Toward Environmental Sustainability - Samsuddin A.; Kaman Z.K.; Mat Husin N. (IOP Publishing Ltd, 2023)
The disastrous events of land flooding prompt an urgency to flood risk management to counterpart this issue with the concept of flood damage divided into four types: direct, indirect, tangible, and intangible. This paper reviewed previous articles regarding flood risk management with a specific focus on methods used for socio-economic impact assessment towards ensuring a sustainable environment. The methodological approach can be sorted into four (4) main types group which are i) historical disaster statistic method, ii) index system method, iii) scenario simulation analysis, and iv) GIS-based approach. Among others, the integrated GIS-based approach becomes the most practical method in conducting socio-economic assessment for flood risk impact. As most of the socio-economic impact-based studies are conducted in western countries, this paper proposed the idea that for different types of countries such as the Asian countries, differences in topography, weather and seasons will lead to a different scale or possibly different types of socio-economic impact, which may require a new approach of assessing the impact. It is also proposed that any socioeconomic and environmental impact assessment needs to explicitly consider both direct and indirect impact. This is to ensure the approach used is holistic, valid, reliable, and more accurately reflect the real nature of the respective flood risk while the gap of the studies also can be identified. Published under licence by IOP Publishing Ltd.